Residential mobility in greater Johannesburg: patterns, associations and educational outcomes amongst children in the birth to twenty cohort - Ginsburg, Carren (My University, 2011)
The United Nations has projected that Africa’s urban population will expand from fourth largest to becoming the second largest of the world’s regions by the year 2050. Patterns of migration and urbanisation have therefore been highlighted as significant focus areas for research and policy. Movement has the potential to result in improved living conditions and well-being, but may also reinforce inequalities and conditions of vulnerability. These consequences may pose particular risks in the case of children, and understanding the patterns, drivers and outcomes associated with child mobility is therefore critical. South Africa provides an important setting in which to explore child movements. The shift within the country from politically controlled migration to movement based on choice has resulted in high levels of mobility both to and within urban areas. Children have been shown to participate in such movements either independently or in conjunction with connected adults. However, there is currently little knowledge of the patterns and consequences of child residential mobility in South Africa, particularly within the urban environment. This PhD thesis attempts to address this research gap. Data from Birth to Twenty, a cohort of South African urban children living in Greater Johannesburg, was used to investigate three central research questions concerning residential mobility of cohort children over a 14 year period. Specifically, the thesis aimed to determine the frequencies and patterns of residential mobility observed over the first 14 years of the children’s lives, to examine the associations with mobility of children over a set of domains relating to the child, the child’s primary caregiver, and the child’s household and to assess the relationships between residential and school mobility and a set of educational outcomes. Routine data collected over the course of the Birth to Twenty study was supplemented with data from a Residential Move Questionnaire, administered to children’s primary caregivers in order to validate and provide additional information concerning the children’s residential movements over the time frame. The research objectives were achieved through the use of cross-sectional and longitudinal analysis techniques applied to these data. In particular, multilevel event-history analysis was used to model the children’s residential movements over time. Of the 3273 children enrolled into the cohort in 1990, two thirds of the children (64%) had moved home at least once by the time they reached 15 years of age. Nonetheless, a third of the children had never moved, indicating stability or a lack of opportunity for movement amongst this urban child population. Mobility was found to be more likely amongst children whose primary caregivers had no formal education and who lived in households with fewer assets and less access to services, suggesting that residential movement within this group of children was more common in the context of disadvantage. Extending these findings to an exploration of children’s educational outcomes revealed some unexpected results. The analyses provided evidence of a positive association between changes in residence and numeracy and literacy scores, and school mobility was found to be associated with grade repetition, however, a negligible relationship was found between residential mobility and school progression. In conclusion, mobility is associated with opportunities for some children in the cohort and challenges or hardships for others. However, even in the instance of movement connected to disadvantage, changes of residence did not prejudice children in terms of the educational outcomes investigated. This is suggestive of children’s possible resilience and adaptability in the face of change and highlights the potential for mobility to influence children’s lives positively. The findings concerning the relationship between mobility and child well-being run counter to trends observed in high-income countries and on that basis, the need for further research into dynamics associated with child mobility in other low- and middle-income country settings is highlighted. There is justification for monitoring child mobility in South Africa; mobility trends provide a valuable indicator of children’s living situations as well as the spatial and social changes occurring in the country more broadly. Keywords: residential mobility; internal migration; urban children; South Africa; eventhistory models; school progression; numeracy and literacy; school mobility
Keywords: residential mobility; internal migration; urban children; South Africa; event-history models; school progression; numeracy and literacy; school mobility